F2F and Online “Live Personalization” of Learning and Implications for Learning Object Repositories and Automated eLearning (A Survey and Analysis) - Hai-Jew, Shalin (My University, 2010)
Learning object repositories, eLearning systems, and other data management systems have built personalization for their learners through intelligent agents, user profiling (personality, role, needs, histories, “interest” measures, live online behaviors, and learning styles metrics), user-directed learning, social networking, and other strategies. “Online ‘Live Personalization’ of Learning and Implications for Learning Object Repositories and Automated eLearning” will explore what F2F (face-to-face) and online instructors bring to their teaching that personalizes the learning for unique individual learners. Finally, some ideas for personalizing learning object (and data) repositories and automated eLearning systems will be explored in the light of human-mediated F2F and online instructor customization strategies.
Keywords: Adaptive learning; Personalization; Automation; Live personalization; Learner profiling; Automated eLearning; Courseware recommendation systems; F2F learning; Online instructor-led learning; Customization